Definition of risk factors for death, end stage renal disease, and thromboembolic events in a monocentric cohort of 338 patients with systemic lupus erythematosus. Issue 12 (1st December 2002) - Manger, K; Manger, B; Repp, R; Geisselbrecht, M; Geiger, A; Pfahlberg, A; Harrer, T; Kalden, J R
Abstract : Background: The survival rate in patients with systemic lupus erythematosus (SLE) has improved dramatically during the past four decades to 96.6% (five year) in the Erlangen cohort, but it is nearly three times as high as in an age and sex matched control population. Reasons for death are mainly cardiovascular diseases (37%) and infections (29%). Objective: To find risk factors existing at disease onset for a severe outcome in the Erlangen cohort. Patients and methods: By using a database of 338 patients with SLE from a single centre, documented at least one to 15 years and including Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) damage score data and index (SDI) and an activity score (European Consensus Lupus Activity Measurement (ECLAM)), a retrospective search was made for risk factors for a severe outcome like death, end stage renal disease (ESRD), and thromboembolic events (TE) in SLE. For this purpose, multivariable Cox regression models were analysed using the statistical package SPSS 10.0 for Windows. Results: The following were defined as risk factors for death at disease onset: male sex (p<0.001, relative risk (RR)=3.5), age >40 at disease onset (p<0.0001, RR=19.9), nephritis (p<0.05, RR=1.6), a reduction of creatinine clearance (p<0.001, RR=1.8), heart disease (p=0.05, RR=1.5), and central nervous system (CNS) disease (p=0.06, RR=1.6). An increase in the SDI of two or more points from the first to the third year of disease was the worst prognostic factor (p<0.0001, RR=7.7). The existence of Ro or nRNP antibodies, or both, was protective (p<0.05, RR =0.1). A low C3 (p<0.01 RR=3.0) and splenomegaly (p<0.01 RR=2.7) at disease onset turned out to be risk factors for ESRD besides a nephritis. In patients with hypertension (p<0.05) and/or high titres of dsDNA antibodies (>70 U/l) (p<0.01) and/or a mean ECLAM score of 4 (p<0.01) in the course of disease, a prevalence of ESRD was recorded in 9% (p<0.05) and 10% (p<0.01), and 8% (p<0.01) v 4% in the whole group. Analysis of risk factors at disease onset for TE identified positive lupus anticoagulant (p=0.17, RR=1.6), cryoglobulins (p<0.05, RR=1.8), and nephritis (p=0.05, RR=1.4), in addition to an age >40 at disease onset. Conclusions: A subgroup of patients in the Erlangen cohort with a typical clinical and serological phenotype at disease onset that is at high risk for a worse outcome was identified. Identification of these white patients at risk at disease onset will enable treatment to be intensified and thereby possibly prevent or better control late stage manifestations.